Genome-wide Screen of Pseudomonas aeruginosa in Saccharomyces cerevisiae Identifies New Virulence Factors - Zrieq, Rafat; Sana, Thibault G.; Vergin, Sandra; Garvis, Steve; Volfson, Irina; Bleves, Sophie; Voulhoux, Romé; Hegemann, Johannes H. (Frontiers in Cellular and Infection Microbiology, 2015)
Pseudomonas aeruginosa is a human opportunistic pathogen that causes mortality in cystic fibrosis and immunocompromised patients. While many virulence factors of this pathogen have already been identified, several remain to be discovered. In this respect we set an unprecedented genome-wide screen of a P. aeruginosa expression library based on a yeast growth phenotype. 51 candidates were selected in a three-round screening process. The robustness of the screen was validated by the selection of three well known secreted proteins including one demonstrated virulence factor, the protease LepA. Further in silico sorting of the 51 candidates highlighted three potential new Pseudomonas effector candidates (Pec). By testing the cytotoxicity of wild type P. aeruginosa vs pec mutants towards macrophages and the virulence in the Caenorhabditis elegans model, we demonstrated that the three selected Pecs are novel virulence factors of P. aeruginosa. Additional cellular localization experiments in the host revealed specific localization for Pec1 and Pec2 that could inform about their respective functions.